2019
DOI: 10.1103/physics.12.134
|View full text |Cite
|
Sign up to set email alerts
|

The Heat in Antiferromagnetic Switching

Abstract: Much theoretical and experimental attention has been focused on the electrical switching of the antiferromagnetic (AFM) Néel vector via spin-orbit torque. Measurements employing multiterminal patterned structures of Pt=AFM show recurring signals of the supposedly planar Hall effect and magnetoresistance, implying AFM switching. We show in this Letter that similar signals have been observed in structures with and without the AFM layer, and of an even larger magnitude using different metals and substrates. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…Correspondingly, within the first generation of experiments on both known compounds with the required structure and AFM ordering, CuMnAs and Mn 2 Au, current pulse induced reversible resistance modifications were reported as evidence for NSOT driven Néel vector rotation [8][9][10][11][12][13] . However, it later became clear that alternative mechanisms such as current pulse induced heat effects 14,15 , electromigration 16 , and rapid quenching induced structural and magnetic modifications 17 can result in resistance modifications similar to the ones reported as well. Additionally, external strain supported Néel vector manipulation in Mn 2 Au was demonstrated 18,19 .…”
supporting
confidence: 55%
“…Correspondingly, within the first generation of experiments on both known compounds with the required structure and AFM ordering, CuMnAs and Mn 2 Au, current pulse induced reversible resistance modifications were reported as evidence for NSOT driven Néel vector rotation [8][9][10][11][12][13] . However, it later became clear that alternative mechanisms such as current pulse induced heat effects 14,15 , electromigration 16 , and rapid quenching induced structural and magnetic modifications 17 can result in resistance modifications similar to the ones reported as well. Additionally, external strain supported Néel vector manipulation in Mn 2 Au was demonstrated 18,19 .…”
supporting
confidence: 55%
“…Correspondingly, within the first generation of experiments on both known compounds with the required structure and AFM ordering, CuMnAs and Mn 2 Au, current pulse induced reversible resistance modifications were reported as evidence for NSOT driven Néel vector rotation [8][9][10][11][12][13]. However, it later became clear that alternative mechanisms such as current pulse induced heat effects [14,15], electromigration [16], and rapid quenching induced structural and magnetic modifications [17] can result in resistance modifications similar to the ones reported as well. Thus, microscopic investigations showing the intended current driven alignment of the staggered magnetization directly are essential.…”
Section: Introductionmentioning
confidence: 99%
“…Electrical manipulation of the AFM Néel vector with the prospect of encoding information was achieved in various AFM compounds, such as CuMnAs, Mn 2 Au, Mn 3 Pt, , Mn 3 Sn, IrMn 3 , NiO, and CoO, via a relativistic mechanism, namely, Néel order spin–orbit torque (SOT)likely without invoking heat or magnetic fields. In strong contrast, recent experiments showed that significant amounts of charge current densities (≥4 × 10 7 A/cm 2 ) beyond the linear ohmic regime of the devices are needed to switch the Néel vector (or the local AFM domains). The power efficiency, the physical mechanism of switching, and the efficiency of the electrical detection method for validating the current-induced microscopic switching of the AFM domains are currently under investigation. Moreover, recent work based on NiO/Pt bilayer devices revealed a current-induced purely thermomagnetoelastic switching mechanism …”
Section: Introductionmentioning
confidence: 99%